2007
DOI: 10.1038/sj.mp.4002061
|View full text |Cite
|
Sign up to set email alerts
|

Linkage on chromosome 14 in a genome-wide linkage study of a broad anxiety phenotype

Abstract: Several linkage studies on anxiety have been carried out in samples ascertained through probands with panic disorder. The results indicated that using a broad anxiety phenotype instead of a DSM-IV anxiety disorder diagnosis might enhance the chance of finding a linkage signal. In the current study, a genome-wide linkage analysis was performed on anxiety measured with a self-report questionnaire whose scores are highly correlated with DSM-IV anxiety disorders. The self-report questionnaire was included in five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…The region on chromosome 1 (p12) also harbors several protein-coding genes (for example WARS2, PI4KB and SCA19), but these also do not play a plausible role in the variance of happiness. Although happiness is often seen as the counterpart of depression, the regions with suggestive linkage for happiness have not been reported for depression so far (e.g., Middeldorp et al, 2008). Furthermore the regions on chromosome 1 and 19 have also not been suggested in a linkage scan for borderline personality disorder features (Distel et al 2008) and a linkage scan for Neuroticism (Wray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The region on chromosome 1 (p12) also harbors several protein-coding genes (for example WARS2, PI4KB and SCA19), but these also do not play a plausible role in the variance of happiness. Although happiness is often seen as the counterpart of depression, the regions with suggestive linkage for happiness have not been reported for depression so far (e.g., Middeldorp et al, 2008). Furthermore the regions on chromosome 1 and 19 have also not been suggested in a linkage scan for borderline personality disorder features (Distel et al 2008) and a linkage scan for Neuroticism (Wray et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Current data point out to roles for genes involved in drug transport, serotonin neurotransmission, neurotrophin signaling and response to stress. Promising linkage results are located in several chromosomes, 3 which highlight the multilocus nature of the genetic vulnerability to MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage studies have revealed several potentially interesting loci located on chromosomes 1, 12 and 14. [4][5][6] Of these, only the locus on chromosome 1q has been identified by different groups independently. 4,5,7 Candidate gene association studies so far have mostly tested monoamine-and neuropeptiderelated genes, giving inconsistent results, which often failed to replicate in independent studies, most likely because of phenotypic diversity, genetic heterogeneity and small sample sizes.…”
Section: Introductionmentioning
confidence: 99%